Assessing nutritional status in a cohort of liver cirrhosis outpatients: A prospective cross-sectional study. Issue 1 (March 2020) - Luong, Rebecca; Kim, Marcellinus; Lee, Alice; Carey, Sharon
Background: Malnutrition impairs prognosis in patients with liver cirrhosis (LC). There is limited research exploring the prevalence of malnutrition in patients with LC in an Australian population and in outpatient settings. Aims: One aim of this study was to investigate the prevalence of malnutrition in patients with LC in an outpatient liver clinic at a tertiary metropolitan hospital in Sydney, Australia, and explore other factors that may be associated with malnutrition. The second aim was to compare different versions of Subjective Global Assessment (SGA). Methods: This cross-sectional study evaluated the nutritional status of 42 prospectively recruited participants by SGA, SGA modified for liver disease (SGA-LD) and patient-generated SGA (PG-SGA). Anthropometric measures and handgrip strength (HGS) were also measured for comparison. Clinical and demographic data were compared with nutritional status. Results: SGA, SGA-LD and PG-SGA yielded the same prevalence of malnutrition of 40% with very good agreement (kappa value = 1.00). Malnourished patients had a lower median HGS% of normal than those who were well-nourished. Malnourished patients also had anthropometric measurements trending towards the lower percentiles of a healthy population. Nutritional status was significantly associated with ethnicity ( p = 0.02) and PG-SGA score ( p < 0.0001). Conclusion: The present study showed that nearly half of our study population were malnourished (40%). Thus, nutrition intervention in terms of nutrition support could improve patient outcomes. It appears that the standard SGA is suitable to assess nutritional status in patients in the early stages of LC compared to more time-consuming SGA versions.